Atypical pneumonia – etiology, epidemiology, clinical presentations, diagnosis and treatment – a review of literature - Grotowska, Magdalena; Zieliński , Szymon; Strawińska, Aleksandra; Wydro, Maria (Quality in Sport, 2026)
Community-acquired pneumonia is a prevalent infectious disease with significant global morbidity and mortality. Atypical pneumonia, is characterized by milder symptoms and different pathogens, including Mycoplasma pneumoniae, Chlamydophila pneumoniae, and Legionella spp. Unlike typical pneumonia caused by Streptococcus pneumoniae and Haemophilus influenzae, atypical pneumonia presents with non-specific symptoms such as headache, fatigue, mild fever, and sore throat. Epidemiologically, atypical pneumonia constitutes over 15% of community-acquired pneumonia cases, with prevalence varying by region. It can be transmitted through aerosolized droplets, direct contact, or environmental exposure. Diagnostic challenges arise from inability of atypical pathogens to be detected via conventional Gram staining or culture techniques, it requires molecular assays like polymerase chain reaction and serological tests. Imaging, including X-ray, computed tomography, and ultrasonography, allow identifying characteristic lung abnormalities, yet their findings often overlap with other respiratory infections. Treatment strategies differ from those for typical pneumonia, as β-lactam antibiotics are ineffective against atypical pathogens due to lack of cell wall. Treatment recommendations include macrolides, tetracyclines, and fluoroquinolones. Complications of atypical pneumonia, though less frequent, can be severe, particularly in high-risk populations. Potential complications range from acute respiratory distress syndrome and cardiovascular conditions to neurological manifestations. Early diagnosis, coupled with targeted antibiotic therapy is essential to improve patients outcomes and reduce complications. This review provides a comprehensive overview of the etiology, clinical presentation, diagnostic challenges, treatment options, and potential complications of atypical pneumonia, emphasizing the need for continued research and improved diagnostic methodologies to enhance patient care.